О проблемах создания и развития виртуальных систем - Тимашова, Л.А. (Управляющие системы и машины, 2017)
Предложен новый метод организации и функционирования предприятий нового поколения – виртуальные предприятия. Разработаны теоретические положения, математические модели, методы и алгоритмы, а также информационные технологии, которые базируются на анализе процессов организации и функционировании виртуальных предприятий. Изложены подходы к созданию интеллектуальных систем управления на примере системы диспетчеризации цеховых систем. Запропоновано новий метод організації та функціювання підприємств нового покоління – віртуальні підприємства. Розроблено теоретичні положення, математичні моделі, методи та алгоритми, а також інформаційні технології, які базуються на аналізі процесів організації та функціонуванні віртуальних підприємств. Подано підходи до створення інтелектуальних систем управління на прикладі системи диспетчеризації цехових систем. Рurpose – to give the idea of problems of creation and development of the virtual enterprises differing in flexibility of management system and intellectual information technologies of its support in conditions of a dynamic external environment. Results. The virtual enterprise is created as system artificially of the heterogeneous enterprises integrated in information space with the single system of control capable to flexibly change the configuration. Strategic advantage of such system is stability and survival in market economy, ability of participants to provide flexibility and integration of resources, an opportunity to quickly form the virtual teams and the virtual environment, to integrate knowledge of competent persons for purposeful activities.